THE INFLUENCE OF PRINCIPAL’S TRANSFORMATIONAL LEADERSHIP ON IMPROVING TEACHERS’ DIGITAL PERFORMANCE AT SMA NEGERI 1 TELUKJAMBE - Ilma Novelia Winata; Maman Suryaman (Pusat Pengembangan Pendidikan dan Penelitian Indonesia, 2026)
ABSTRACT The Industrial Revolution 4.0 and digital transformation have reshaped education, demanding strong digital competencies from teachers. However, many teachers still underutilize digital tools, creating a gap between expectations and reality. Principals play a strategic role in bridging this gap through effective leadership. This study aims to analyze the influence of the principal’s transformational leadership on teachers’ digital performance at SMA Negeri 1 Telukjambe. A quantitative correlational design was employed with a population of 52 teachers and a sample of 50 selected through simple random sampling. Data were collected using validated questionnaires measuring transformational leadership (idealized influence, inspirational motivation, intellectual stimulation, individualized consideration) and digital performance (LMS usage, digital content creation, digital media utilization, digital communication, grade data management). Multiple linear regression analysis using SPSS showed that transformational leadership significantly influences digital performance (R² = 0.672). Inspirational motivation and intellectual stimulation were the strongest predictors. The study concludes that principals should strengthen individualized consideration through structured mentoring, while policymakers should support digital training and infrastructure. ABSTRAK Revolusi Industri 4.0 dan transformasi digital telah mengubah lanskap pendidikan, menuntut guru memiliki kompetensi digital yang kuat. Namun, banyak guru masih kurang memanfaatkan alat digital sehingga terjadi kesenjangan antara harapan dan realitas. Kepala sekolah berperan strategis untuk menjembatani kesenjangan ini melalui kepemimpinan yang efektif. Penelitian ini bertujuan menganalisis pengaruh kepemimpinan transformasional kepala sekolah terhadap kinerja digital guru di SMA Negeri 1 Telukjambe. Pendekatan kuantitatif dengan desain korelasional digunakan pada populasi 52 guru dengan sampel 50 guru yang dipilih secara acak sederhana. Data dikumpulkan menggunakan kuesioner yang divalidasi untuk mengukur kepemimpinan transformasional (pengaruh ideal, motivasi inspiratif, stimulasi intelektual, perhatian individual) dan kinerja digital (penggunaan LMS, pembuatan konten digital, pemanfaatan media digital, komunikasi digital, pengelolaan nilai). Analisis regresi linear berganda dengan SPSS menunjukkan bahwa kepemimpinan transformasional berpengaruh signifikan terhadap kinerja digital (R² = 0,672). Motivasi inspiratif dan stimulasi intelektual merupakan prediktor terkuat. Simpulannya, kepala sekolah perlu memperkuat perhatian individual melalui mentoring terstruktur, sementara pembuat kebijakan perlu mendukung pelatihan digital dan infrastruktur.